2011
DOI: 10.1556/abiol.61.2011.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of bacteriocins produced by twoLactobacilusstrains with probiotic properties

Abstract: The probiotic characteristics of Lactobacillus brevis BG18 and Lb. plantarum BG33, isolated from traditional Turkish Tulum cheese were assessed. These two bacteriocinproducer strains exhibited good probiotic characteristics such as resistance in media containing 0.3% bile salt, pepsin (3 mg mL⁻¹), and pancreatine (1 mg mL⁻¹) as well as acid resistance at pH 2. They were also adhered to Caco-2 epithelial cells in a manner comparable to Escherichia coli LMG3083 (ETEC) and Salmonella Typhimurium SL1344. The strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Sarantinopoulos et al (2002) also concluded that the complex environment of Feta cheese, which is very similar to white-brined cheese, thoroughly interferes with bacteriocin production levels of bacteriocinogenic starter or co-cultures and there is no guarantee for their in situ antimicrobial efficiency. This is also confirmed by the study of Uymaz et al (2011) who demonstrated a greater and broad inhibitory activity of Lb. plantarum BG33 against all the tested indicator strains, including S. aureus, by the agar overlay assays.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Sarantinopoulos et al (2002) also concluded that the complex environment of Feta cheese, which is very similar to white-brined cheese, thoroughly interferes with bacteriocin production levels of bacteriocinogenic starter or co-cultures and there is no guarantee for their in situ antimicrobial efficiency. This is also confirmed by the study of Uymaz et al (2011) who demonstrated a greater and broad inhibitory activity of Lb. plantarum BG33 against all the tested indicator strains, including S. aureus, by the agar overlay assays.…”
Section: Resultssupporting
confidence: 65%
“…The synthesis of plantaricin-like bacteriocin (400 AU mL -1 ) with low heat stability but high resistancy to lipase by Lb. plantarum BG33, was defined in the previous study, 25 (2019) 401-408 403 including its antimicrobial and probiotic potential (Uymaz et al 2011). The reference strain of S. aureus ATCC 6538 was cultivated in tryptic soy broth (TSB; Merck, Germany) at 35-37 °C for 18-24 h and subcultivated twice in sterile reconstituted skim milk before use in white-brined cheese production.…”
Section: Culturesmentioning
confidence: 99%
“…Meanwhile, molecular weight of this bacteriocin determined by tricine-SDS-PAGE was approximately 12.8 kDa (Fig. 1), which was relatively larger than that of bacteriocin DF01 (8.2 kDa) from L. brevis DF01 and brevicin 27 (5.2 kDa) from L. brevis SB27 (31,33).…”
Section: Not Determinedmentioning
confidence: 91%
“…cereus ATCC 11778 (30). Bacteriocin of L. brevis BG18 isolated from traditional Turkish Tulum cheese was able to inhibit growth of Gram-positive bacteria such as L. monocytogenes, Clostridium botulinum, S. aureus, and B. cereus (31).…”
Section: Not Determinedmentioning
confidence: 99%
“…This suggests that L. plantarum SB1 and L. acidophilus SB4 can be used not only against intestinal or foodborne pathogenic microorganisms but also against food spoilage bacteria such as Listeria monocytogenes. The inhibitory activity of probiotic bacteria against pathogenic is associated to the production of organic acid or mostly the production of antimicrobial proteins called bacteriocins [18][19][20][21][22][23][24]. For the isolates selected in this study, further studies need to be done in order to characterize and identify the nature of their antimicrobials molecules released during growth.…”
Section: Resultsmentioning
confidence: 99%